1996
DOI: 10.5014/ajot.50.8.676
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Strategies for the Development of Clinical Reasoning

Abstract: A primary aim of occupational therapy education is to teach students how to think like practitioners, that is, how to engage in clinical reasoning. Since the early 1980s, occupational therapy clinical reasoning research has elucidated a language that describes the various types of thinking therapists use in clinical practice, a language that has the potential to make previously tacit thought processes accessible to conscious examination and improvement. Occupational therapy educators can use that language to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 19 publications
1
63
0
2
Order By: Relevance
“…Cognitive Processing (ranked 1 st ) is relevant during the cognitive learning stage and includes critical thinking, decision-making, and problem-solving. One could surmise the value of reflective processes [32][33][34][35] to OMPT education and skill development 34 , based on their importance in hypothesis testing 32,36,37 and management strategy development 38 . Adaptation (ranked 2 nd ) characterizes the associative psychomotor learning stage.…”
Section: Motivationmentioning
confidence: 99%
“…Cognitive Processing (ranked 1 st ) is relevant during the cognitive learning stage and includes critical thinking, decision-making, and problem-solving. One could surmise the value of reflective processes [32][33][34][35] to OMPT education and skill development 34 , based on their importance in hypothesis testing 32,36,37 and management strategy development 38 . Adaptation (ranked 2 nd ) characterizes the associative psychomotor learning stage.…”
Section: Motivationmentioning
confidence: 99%
“…The process of clinical reasoning is multifarious and clinicians of all levels of ability and experience look to develop the cognitive elements of decision-making to enhance practice and improve patient-care (Benner 1984;Higgs 1992;Neistadt 1996). This synthesising process involves considering many facets of patient data, clinician experience, clinician knowledge, and the literature (Higgs and Jones 2008;Simmons 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of each is to better prepare student practitioners for the diverse challenges of reasoning within routine clinical practice. A review of the literature found use of multimedia (audio, video and/or text) delivered asynchronously online using chat rooms and message boards, and live simulations with students functioning in the role of therapist and/or client in a classroom environment as methods to teach clinical reasoning (Hedge, Pickens, & Neville, 2015;Lysaght & Bent, 2005;Neistadt, 1996;Scaffa & Wooster, 2004). Additional instructional activities designed to promote clinical reasoning in students include interviewing and occupational profile assignments, treatment planning assignments, ethical case studies, evidence-based decision-making assignments, and student reflection and journaling assignments (Coker, 2010;Mattingly & Fleming, 1994;Neistadt, Wight, & Mulligan, 1998;Peloquin & Davidson, 1993;Tickle-Degnen, 2000).…”
Section: Narrative Reasoningmentioning
confidence: 99%
“…Narrative reasoning emerges during the clinical process as the therapist and the client collaborate on intervention goals, strategies, and solutions (Mattingly & Fleming, 1994;Neistadt, 1996).…”
Section: Narrative Reasoningmentioning
confidence: 99%
See 1 more Smart Citation